Advancing women's status : women and men together? : critical reviews and a selected annotated bibliography - Bruyn, Maria de ed. (Royal Tropical Institute AmsterdamNL, 1995)
Focuses on gender relations, namely the social, economic, political and legal roles of women and men in society. Highlights four themes from a gender perspective viz. women's status and rights; education and training; economic participation; and, sexual and reproductive health. Provides an annotated bibliography for each of the themes.